The Holy Qur’an and its impact on eliciting the morphological significance between the old and the modern (Journal of the College of Basic Education, 2022)
The Holy Qur’an is an argument in the Arabic language and one of the most important evidences of industry for the scholars of the circleThe scholars of morphology studied the buildings and assigned a specific meaning to each building until it became clearThe parameters of the study of the morphological significance, and they inferred this significance from the data of the Qur’anic text, and they are inVarying degrees in the extent to which the significance of the building is derived from the Holy Qur’an »; This research aims to clarifyThe efforts of scholars to what extent they depend on the Holy Qur’an in extracting the significance of buildings, and this is done through mentioningTexts from their writings, discussing their opinions and comparing them with the efforts of modernists and scholars of linguistic academies.an introductionirrigation.